PERAWATAN LUKA PADA PASIEN FRAKTUR TIBIA FIBULA DENGAN MENGGUNAKAN NACL 0,9% DI DESA CISUMUR KECAMATAN GANDRUNGMANGU KABUPATEN CILACAP - Yoeda Bhakti Karthica; Sudiarto; Fida Dyah Puspitasari (Jurnal Ilmiah Medsains, 2023)
Fracture is a fracture that occurs continuously in the bone structure, nothing more than a tear, shrink, or tearing of the cortex. Closed fractures are the overlying skin tissue that remains intact. If the skin and one of the body cavities are punctured or penetrated it s cllaed an open fracture. Wound care using 0,9% NaCl is a technique to prevent infection in the wound. 0,9% NaCl liquid is a liquid that is very effective in the healing process because it s in accordance with the salt content in the body. Purpose of this study is to descriptife research type with a case study design. Results show that wound care 3 meetings decreased exudate so that the wound improved and protected from bacteria that could cause infection. Conclusion of this study is wound care in patients with tibia and fibula fractures has decreased exudate.